Efeitos da política fiscal sobre a dinâmica macroeconômica : dinâmica da dívida pública brasileira e seus efeitos no período recente - Santos Filho, Washington Valeriano dos (2014)
This work deals with the theme of Fiscal Policy, and more specifically, their effects on macroeconomic dynamics. The paper analyzes the dynamics of public debt and its effects in the recent period. The overall objective was to verify if public debt is enriching effect, if the debt is there real output growth of the economy. This paper discusses the debate about the issue of public debt, presents different views on the effects of fiscal policy on macroeconomic dynamics, verifies what has been the result found by different authors for the brazilian economy and analyze the (post-real) brazilian case.